Viral DNA synthesized in vitro by avian retrovirus particles permeabilized with melittin. I. Kinetics of synthesis and size of minus- and plus-strand transcripts. - Boone, L R (1981)
We have examined the kinetics of synthesis of minus [(-)]- and plus [(+)]-strand viral DNA in melittin-permeabilized avian retrovirus particles. The reaction was biphasic. There was a very rapid initial rate, followed, after approximately 1 h, by a lower rate. Many discrete bands of subgenomic-length (-) strands were produced after 10 and 20 min of synthesis; genome-length (7.7-kilobase [kb]) (-) strands were detected within 30 min. Extension to an 8.0-kb (-)-strand species was evident by 60 min. This extension was inhibited by actinomycin D. Synthesis of (+) strands (which is also inhibited by actinomycin D) began early, before any (-) strands were completed, and continued for more than 4 h beyond the time when synthesis of full-length DNA had terminated. Two distinct species of (+)-strand DNA, 0.27 and 0.35 kb, could be observed at the earliest times. Their presence was quickly obscured by subsequent formation of (+)-strand molecules of molecular length between 0.2 and 2.0 kb.